Neuromuscular Age-Related Adjustment of Gait When Moving Upwards and Downwards - Dewolf, Arthur H.; Sylos-Labini, Francesca; Cappellini, Germana; Zhvansky, Dmitry; Willems, Patrick A.; Ivanenko, Yury; Lacquaniti, Francesco (Frontiers in Human Neuroscience, 2021)
Locomotor movements are accommodated to various surface conditions by means of specific locomotor adjustments. This study examined underlying age-related differences in neuromuscular control during level walking and on a positive or negative slope, and during stepping upstairs and downstairs. Ten elderly and eight young adults walked on a treadmill at two different speeds and at three different inclinations (0°, +6°, and −6°). They were also asked to ascend and descend stairs at self-selected speeds. Full body kinematics and surface electromyography of 12 lower-limb muscles were recorded. We compared the intersegmental coordination, muscle activity, and corresponding modifications of spinal motoneuronal output in young and older adults. Despite great similarity between the neuromuscular control of young and older adults, our findings highlight subtle age-related differences in all conditions, potentially reflecting systematic age-related adjustments of the neuromuscular control of locomotion across various support surfaces. The main distinctive feature of walking in older adults is a significantly wider and earlier activation of muscles innervated by the sacral segments. These changes in neuromuscular control are reflected in a reduction or lack of propulsion observed at the end of stance in older adults at different slopes, with the result of a delay in the timing of redirection of the centre-of-mass velocity and of an unanticipated step-to-step transition strategy.